The Effect of Entrepreneurship Learning, Social Environment, and Creativity on Entrepreneurial Interest: The Mediating Role of Entrepreneurial Attitude - Said Hamzali; Arwin Arwin (Pinisi Journal of Entrepreneurship Review, 2025)
Learning is not merely the accumulation of knowledge, but a cognitive process that induces behavioral changes in individuals. In the context of higher education, entrepreneurship learning plays a vital role in shaping students’ mindset and interest toward entrepreneurship. This study aims to examine both the direct and indirect effects of entrepreneurship learning, social environment, and student creativity on entrepreneurial interest, with an entrepreneurial attitude serving as a mediating variable. A quantitative explanatory descriptive approach was adopted, involving a sample of 100 students from a public university in Indonesia selected through proportional random sampling. Data was collected via structured questionnaires and analyzed using path analysis techniques. The findings demonstrate that entrepreneurship learning, social environment, and student creativity have both direct and mediated effects on entrepreneurial interest through entrepreneurial attitude. Entrepreneurial attitude significantly influences entrepreneurial interest, confirming its critical mediating role. These results highlight the importance of combining cognitive, social, and creative factors to strengthen students’ entrepreneurial readiness. This study offers practical insights for educators and policymakers to enhance entrepreneurship curricula by integrating skill-building, creativity stimulation, and real-world social exposure. Future research is recommended to explore extended models with additional variables and utilize mixed method approaches for a deeper understanding of entrepreneurial behavior in academic settings